2019
DOI: 10.1055/s-0039-1698383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multi-modality Monitoring Using Direct Electrical Stimulation to Determine Corticospinal Tract Shift and Integrity in Tumors using the Intraoperative MRI

Abstract: Introduction Preserving the integrity of the corticospinal tract (CST) while maximizing the extent of tumor resection is one of the key principles of brain tumor surgery to prevent new neurologic deficits. Our goal was to determine the impact of the use of perioperative diffusion tensor imaging (DTI) fiber-tracking protocols for location of the CSTs, in conjunction with intraoperative direct electrical stimulation (DES) on patient neurologic outcomes. The role of combining DES and CST shift in intraoperative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Additionally, subcortical MEP mapping can be of further help to evaluate the distance towards the corticospinal tract during resection of motor-eloquent lesions thus reducing the risk of neurological deficit [50]. Combining information about intraoperative corticospinal tract together with direct electrical stimulation in the setting of IoMRI can enhance resection of brain tumors, with up to 77% having a GTR, as suggested by some authors [18].…”
Section: Cortical Mappingmentioning
confidence: 96%
“…Additionally, subcortical MEP mapping can be of further help to evaluate the distance towards the corticospinal tract during resection of motor-eloquent lesions thus reducing the risk of neurological deficit [50]. Combining information about intraoperative corticospinal tract together with direct electrical stimulation in the setting of IoMRI can enhance resection of brain tumors, with up to 77% having a GTR, as suggested by some authors [18].…”
Section: Cortical Mappingmentioning
confidence: 96%
“…136 During surgery, intermittent stimulation of the motor cortex is performed when the MEP signal decreases, and subcortical stimulation is performed there to expand the resection range and approach the corticospinal tract. 14,31,40 A correlation has been reported between subcortical…”
Section: Neurophysiological Monitoringmentioning
confidence: 97%
“…iMRI can permit re-registration of neuronavigation systems to account for brain shift during surgery. To enhance functional navigation, iMRI can also permit diffusion tensor imaging (DTI), allowing for preservation white matter connections such as the corticospinal tract while maximizing the extent of resection [ 81 ]. In 135 glioblastoma patients who underwent resection, Kuhnt et al found that residual contrast-enhancing tumor was identified by iMRI in 65% of cases, leading to additional resection in 19 cases [ 82 ].…”
Section: Image Guidancementioning
confidence: 99%
“…IOUS has been shown to have high sensitivity and specificity both adult and pediatric brain tumors [92]. Ultrasound is a highly multi-modal technology, and may be used to determine tissue composition with elastosonography [81], detect flow patterns in tumor vessels with micro vessel power doppler [93] and may be fused with MR imaging to reduce radiation with fluoroscopy [94].…”
Section: Intraoperative Ultrasoundmentioning
confidence: 99%